STUDI DESKRIPTIF CUSTOMER SATISFACTION YANG DI UKUR MELALUI GAP ANTARA PERSEPSI DAN EKSPEKTASI SERVICE QUALITY DI SURABAYA PLAZA HOTEL - Koean Andrianto (CALYPTRA, 2016)
This study aims to identify and analyze Customer Satisfaction is measured through a gap between the perception and expectations of the Service Quality in Surabaya Plaza Hotel. This research was conducted at the business guests who stay at least 2 times in the last 6 months and have at least high school education. Data processing was performed using SPSS windows 18.00. The sampling technique used was non-probability sampling with the type of judgmental sampling. Data obtained directly from respondents who meet the characteristics specified population by distributing questionnaires. The samples used in this study was 100 respondents. The results of this study showed a Customer Satisfaction is measured through a gap between the perception and expectations of the Service Quality in Surabaya Plaza Hotel